Evaluasi Kebijakan Pamsimas Dalam Keberlanjutan Sistem Penyediaan Air Minum Dan Sanitasi Di Kabupaten Bone Bolango - Ibrahim, Rizkiyanto; Irawaty Igirisa; Rizal (Journal of Economic, Business, and Administration (JEBA), 2023)
The aims of this study were to: 1) find out the evaluation of the Village Pamsimas Policy in the sustainability of the Community-based Water Supply and Sanitation Supply System in Bone Bolango Regency; 2) Knowing the determinants of the sustainability of the Water Supply and Sanitation Supply System in sustainable villages in Bone Bolango Regency. This research uses descriptive research with a qualitative approach. With data analysis techniques, consisting of data reduction, data presentation and drawing conclusions. The results of the study: 1) Evaluation of the Pamsimas policy in Tinemba Village in terms of indicators of effectiveness, efficiency, equity, responsiveness and accuracy shows that the Pamsimas program in Tinemba Village is well implemented up to the program sustainability stage; 2) Evaluation of Pamsimas policies in East Bulotalangi Village in terms of indicators of effectiveness, efficiency, equity, responsiveness, and accuracy shows that the Pamsimas program in East Bulotalangi Village at the stage of program implementation is running well. However, at the sustainability stage, the Pamsimas program facilities become partially functional. Because at the program sustainability stage the indicators of effectiveness and responsiveness were not achieved; 3) Evaluation of the Pamsimas policy in Patoa Village in terms of indicators of effectiveness, efficiency, equity, responsiveness and accuracy shows that the Pamsimas program in Patoa Village at the stages of program implementation and sustainability is not going well. So that the pamsimas program that was carried out in Patoa Village did not provide benefits to the community.